PERAN PERTANIAN PERKOTAAN DALAM MENDUKUNG PEMBANGUNAN BERKELANJUTAN (STUDI KASUS: PERTANIAN AKUAPONIK DI KOTA SEMARANG) - Lutfiyatul Wahdah; Maryono Maryono (PROSIDING SNAST, 2018)
Population increasing is one of the phenomena occurring in urban areas. It causes the increase in land use change from open space to be a built-up area. Limitations of open space due to development make agricultural activities rarely found in the urban area. Urban farming is one of the new cultivation methods in agricultural activities and suitable to developed on limited land. The aquaponic’s concept as one of the urban farming combines fish and vegetable cultivation. The development of aquaponic concepts can support sustainable development and address urban issues. Therefore, this study aims to identify the characteristics of urban agriculture and analyze the role of urban agriculture in supporting the sustainable urban development. This research case study located Semarang City and the research method used quantitative descriptive. The result of this research are: a) Characteristics of urban farmers in urban areas are between 30-50 years old, men, married, high school, and family members more than 4 peoples. b) Characteristics of urban agricultural activities in urban areas do not require extensive land, landowner status, vertical farming, and urban agriculture are used for personal use. Urban agricultural activities can support sustainable urban development during urban agriculture can provide economic benefits in additional income, social benefits in using of leisure time and mutual assistance among the community, environmental benefits in optimizing the use of open space, reducing air pollution, appending home aesthetics, and improve the environmental quality